Social guarantees of employees under martial law in Ukraine - Leschukh, Danylo; Yakymets, Oleksii; Polishko, Natalia; Kantsir, Volodymyr; Furyk, Ihor (Interacción y Perspectiva, 2024)
In the scientific article, with the help of general philosophical and special methods of scientific knowledge, social guarantees of workers under martial law in Ukraine are investigated. The definition and clarified the essence of social protection as one of the key categories of social policy of the state. It is emphasized that social protection of employees requires the definition of a complex of large-scale measures at the state, sectoral, regional and production levels, increasing the mutual responsibility of employers and employees, improving the organization of prevention of accidents and diseases at work. The main directions of increasing the level of social protection of the employee are determined. The arguments concerning the necessity in case of termination of the employment contract during the period of martial law to ensure the unhindered and actual implementation, protection and protection of labor rights primarily of such workers as mobilized, internally displaced persons, pregnant and minors. The expediency of providing additional guarantees for employees working under fixed-term employment contracts under the conditions of a special legal regime is substantiated.